Developing constructs of anatomy education environment measurement: A Delphi study - Hadie, Siti Nurma Hanim; Hassan, Asma; Mohd Ismail, Zul Izhar; Asari, Mohd Asnizam; Khan, Aaijaz Ahmed; Kasim, Fazlina; Mohd Yusof, Nurul Aiman; Abdul Manan@Sulong, Husnaida; Tengku Muda, Tengku Fatimah Murniwati; Arifin, Wan Nor; Yusoff, Muhamad Saiful Bahri (Elsevier, 2014)
Inadequate anatomical knowledge due to unsatisfactory anatomy education environment has contributed to poor clinical performance among medical graduates. Unfortunately, no specific environment measurement tool is available. Delphi technique was conducted to identify the anatomy education environment components and their items. It involved identification of possible components and their definitions by nine anatomists which were then appraised and verified, getting critical appraisal from five medical educationists, determining suitable items for each component and finally appraised by content experts. Eleven components with 129 items that might represent the anatomy education environment were proposed. Further validation is required to determine its psychometric properties.